2000
DOI: 10.1002/(sici)1098-1136(20000215)29:4<305::aid-glia2>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine modulates TNF-? secretion and neurotoxicity induced by microglial activation

Abstract: Among the chemokine family, fractalkine shows unusual properties: it exists as a membrane‐bound and soluble protein, and both fractalkine and its receptor CX3CR1 are expressed predominantly in the central nervous system. In rat cell culture models, the chemokine fractalkine was expressed in neurons and microglia, but not in astrocytes and its receptor exclusively localized to microglial cells, where its expression was downregulated by treatment with the bacterial endotoxin (LPS). In microglial cultures, LPS (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(237 citation statements)
references
References 46 publications
13
223
0
1
Order By: Relevance
“…There is evidence to suggest that FKN has anti-inflammatory activity. FKN suppresses LPS-induced TNF-␣ and IL-6 secretion in microglial cultures in vitro (42,58). Furthermore, in rat models of neuroinflammation induced by cerebral injection of LPS, neutralization of endogenous brain FKN with specific antibodies was associated with potentiation of LPS-induced release of inflammatory mediators, including TNF-␣ and 8-isoprostane, a marker of oxidative stress (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to suggest that FKN has anti-inflammatory activity. FKN suppresses LPS-induced TNF-␣ and IL-6 secretion in microglial cultures in vitro (42,58). Furthermore, in rat models of neuroinflammation induced by cerebral injection of LPS, neutralization of endogenous brain FKN with specific antibodies was associated with potentiation of LPS-induced release of inflammatory mediators, including TNF-␣ and 8-isoprostane, a marker of oxidative stress (59).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ had no effect on IFN-␥-and TNF-␣-induced JNK phosphorylation [58,208.8 Ϯ 8,017.432 relative light units (RLU) vs. 57,256.8 Ϯ 7,367.463 RLU in the absence and presence of TGF-␤, n ϭ 4, P Ն 0.05]. Dexamethasone, however, had a small but significant inhibitory effect on IFN-␥-and TNF-␣-induced JNK phosphorylation (58,208.750 Ϯ 8,017.432 RLU vs. 46,811 Ϯ 6,183.3 RLU in the absence and presence of dexamethasone, n ϭ 4, P Յ 0.05). TGF-␤ and dexamethasone had no direct effect on JNK phosphorylation, and the total protein content of JNK remained unchanged under all treatment conditions (data not shown).…”
Section: Role Of Erk P38 and Jnk In Cytokine-induced Asmc Fkn Produmentioning
confidence: 99%
“…A protective and anti-inflammatory role of CX3CL1 has also been suggested in AD. 85,86 Cardona et al, 87 using three different in vivo models, also showed that the inhibition of CX3CR1 dysregulates microglial responses resulting in neurotoxicity. These data suggest preferentially a protective role of CX3CL1-CX3CR1 signaling, and raise concerns that CNS penetration by CX3CR1 antagonists might increase neuronal vulnerability.…”
Section: Multiple Sclerosis: a Jumble Of Chemokines And Chemokine Recmentioning
confidence: 97%
“…83 In addition to increasing phagocytosis, FKN has also been associated with anti-inflammatory actions such as providing neuroprotection during glutamate toxicity, 84,85 modulating TNF-α secretion by microglia, 86 and promoting proliferative effects, 87,88 which may all have important roles in different settings of cell clearance. However, clarification is needed as to which processed form is responsible for these FKN effects.…”
Section: Steps Involved In Clearancementioning
confidence: 99%